Analisis Pembingkaian Pemberitaan Pedofilia di Lembaga Pendidikan Islam Pada Media Online Tribunnews.com - Dafara, Nur Syamsi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study uses framing analysis to determine the reality constructed by the media through the frame displayed on a news story. The formulation of the problem in this study aims to find out the framing of news about pedophilia in Islamic educational institutions constructed by online media Tribunnews.com based on the perspective of Zhongdang Pan and Gerald M. Kosicki. This research method is descriptive qualitative. The research corpus consisted of five news stories published during the period from January to April 2022 using purposive sampling techniques. The results of the study at the syntactic level display the news of pedophilia in the Islamic educational environment ranging from headlines, leads, background information, source quotations, statements, closing chronologically with writing using an inverted pyramid structure. The construction of reality formed Tribunnews.com in the reporting of pedophilia in the Islamic religious education environment often uses long but representative news headlines with the content of the news. In its reporting, Tribunnews.com still prioritize objectivity in constructing events based on the delivery of source information in news texts. The construction of Tribunnews.com news related to pedophiles in Islamic religious educational institutions is presented by highlighting a certain side to the aspect of morality to attract the attention of the reader.